A new architecture for ATM cell routing based on Banyan network - Ruggiero, Carlos Antônio; Colombini, Angelo Cesar (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2000: Anais do XII Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.2000.41233, 2000)
Routing in ATM switches is very complex. The complexity increases when the applications require multicast capabilities. Both unicast and multicast traffic and also the Banyan network have only N² crossing points. Because of that, there is an inevitable contention for the same output link and a bottleneck point. It is important to mention that cost and speed of operation are essential requirements in ATM. The easy solution to this problem would be the buffer strategy. However, a better option is to modify the Banyan network in such a way that could keep its characteristics of auto routing, allowing a disassociation of Unicast and Multicast cell traffic inside the routing structure.